2013
DOI: 10.1021/mp4001316
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Pre-Existing Immunity to Adenovirus in Rodents: Immunological Requirements for Successful Development of a Recombinant Adenovirus Serotype 5-Based Ebola Vaccine

Abstract: Pre-existing immunity (PEI) to human adenovirus serotype 5 (Ad5) worldwide is the primary limitation to routine clinical use of Ad5-based vectors in immunization platforms. Using systemic and mucosal PEI induction models in rodents (mice and guinea pigs), we assessed the influence of PEI on the type of adaptive immune response elicited by an Ad5-based vaccine for Ebola with respect to immunization route. Splenocytes isolated from vaccinated animals revealed that immunization by the same route in which PEI was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 80 publications
2
25
0
Order By: Relevance
“…However, it is noteworthy that in the majority of previous studies, preexisting anti-AdHu5 immunity was generated by systemic AdHu5 infection. As AdHu5 virus is a respiratory pathogen in humans and recent evidence suggests a differential immune-regulatory effect by the mucosal route of induction of anti-AdHu5 immunity, 61,62 in this study we generated preexisting anti-AdHu5 immunity by respiratory route of wild-type AdHu5 infection that generated anti-Ad5-neutralizing antibody titers in both the lung and circulation, similar to the levels seen in humans. 62 Thus, this method is not only clinically relevant but is also relevant to the investigation of AdCh-based respiratory mucosal TB vaccination strategies.…”
Section: Discussionmentioning
confidence: 67%
“…However, it is noteworthy that in the majority of previous studies, preexisting anti-AdHu5 immunity was generated by systemic AdHu5 infection. As AdHu5 virus is a respiratory pathogen in humans and recent evidence suggests a differential immune-regulatory effect by the mucosal route of induction of anti-AdHu5 immunity, 61,62 in this study we generated preexisting anti-AdHu5 immunity by respiratory route of wild-type AdHu5 infection that generated anti-Ad5-neutralizing antibody titers in both the lung and circulation, similar to the levels seen in humans. 62 Thus, this method is not only clinically relevant but is also relevant to the investigation of AdCh-based respiratory mucosal TB vaccination strategies.…”
Section: Discussionmentioning
confidence: 67%
“…Several studies have been conducted on the application of gene therapies using Ad5-based vaccines for the treatment of cancer or chronic virus infections, which have shown that the immunogenicity responses specific for Ad proteins and for transgene-encoded proteins induced by vaccines could have a significant impact on the efficacy of a recombinant Ad vaccine [23][24][25]. Thus, an essential aspect to ensure the efficacy of virus-vector drugs is to comprehensively and accurately evaluate their immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…This species difference in vaccine efficacy may relate to fundamental mechanistic differences in infection or immune protection for each animal model, or could simply reflect more subtle requirements for the level or balance of specific immune responses. While not predictive of protection in primates, rodent models were crucial for identifying functional genetic vector systems, targeting immunogenic virus proteins, and defining potential immune correlates of protection [2,[4][5][6].…”
Section: Gene-based Vaccination Demonstrates Protection Of Macaquesmentioning
confidence: 99%